Growth, biomass yield, and proximate composition of sea vegetable, Caulerpa macrodisca (Bryopsidales, Chlorophyta) cultured in tank - Zuldin, Wahidatul Husna; Shaleh, Sitti Raehanah Muhamad; Shapawi, Rossita (2019)
Caulerpa macrodisca Decaisne, 1842 is a siphonous green macroalgae that has been reported to be distributed around southwest Asia (Sri Lanka); South China Sea; southeast Asia (Indonesia, Philippines, Singapore, and Vietnam); and Pacific islands (Samoan archipelago). However, the cultivation and consumption of C. macrodisca in the reported region were very uncommon due to the limited research on this green seaweed species. Thus, this study reported the growth rate, biomass yield, and proximate composition of C. macrodisca cultured in the tank. The C. macrodisca was successfully grown in the tank within 40d under the following conditions: salinity (30.29?32.18ppt), temperature (28.03?31.42°C), dissolved oxygen level (DO; 4.75?5.21mg L-1), pH (7.62?8.06), and light intensity (50.77?87.55μmol photons m?2 s?1). The average specific growth rate of C. macrodisca in the tank was as high as 5.13±0.06% g day?1 ? as indicated by average mass increments in terms of fresh weight (from 16.56±0.17g to 129.30 ±2.83g), disc portion (from 30?60 discs to >100 discs in each tank), disc diameter (from 0.24±0.33cm to 2.42±0.18cm), and frond length (from 0.82±0.14cm to 14.51±0.27cm). The average biomass yield of C. macrodisca in the tank was 114.58±0.67 g m?2 day?1. A proximate analysis was performed on the harvested C. macrodisca ? with values (%) of 20.84±0.41, 19.74±0.24, 1.34±0.05, 21.79±0.08, and 93.35±0.13 for crude protein, crude fibre, crude lipid, crude ash, and moisture content, respectively ? comparable to the proximate content of wild C. macrodisca except for the slightly lower crude fiber content and higher ash content. This study suggested that C. macrodisca would perform equally well in tank with good proximate composition. In conclusion, this study is significant to provide a baseline data of an alternative Caulerpa species (C. macrodisca) for cultivation. (Author's abstract)